The Interpretation of the Verbal Probability Expressions Used in The IFRS – The Differences Observed Between Polish and British Accounting Professionals - Katarzyna Kolesnik; Sylwia Silska-Gembka; Jerzy Gierusz (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: Do Polish and British accounting professionals interpret verbal probability expressions (VPEs) differently when presented with identical excerpts from IFRS? Motivation: Our research has been motivated by the ongoing debate of consistent interpretation of VPEs. The major difficulty in the interpretation of these terms is the imperative for the accountants to express their individual subjective judgements. Previous research shows that these expressions may have low communication efficiency (Simon, 2002) as they give way to 'wide variations in interpretation' (Chesley, 1986: 196). The lack of consistency in the interpretation of VPEs may limit the usefulness of the financial statements prepared on their basis (Simon, 2002). Idea: We examine the interpretational differences between Poles and the British. We also survey whether the principle of prudence will impact the interpretation manner of the Polish and the British accounting professionals. Data: For the purpose of our study we distributed a questionnaire. 332 questionnaires from Poland and 75 questionnaires from the UK included answers that were subject to the analysis. Tools: We asked a sample of professional accountants from Poland and the UK to interpret the "in context" VPEs used in IFRS establishing the threshold for recognition of various accounting elements. Findings: Our results show that there are differences in the manner the Poles and the British interpret VPEs. Additionally, we indicate that the Polish accountants' attachment to the prudence principle affects their manner of interpretation. However, we were not able to state whether this principle would not affect the level of probability assigned by the British accountants. Contribution: Our paper provides the first comparative results for Poland and the UK, in terms of surveying professional judgement under with relation to the IFRS.
Keywords: M41; 650; IFRS; interpretation; professional judgement; verbal probability expressions